New Zealand children’s spirituality in Catholic schools: teachers’ perspectives - Kennedy, Anne (International journal of children's spirituality, 2006)
This article discusses the findings of a small‐scale study undertaken with a sample of 10 teachers in Catholic schools in New Zealand. Spirituality is recognised as an important dimension of Catholic schools and this study explored the teachers’ perspectives of their own understanding of spirituality, of children’s spirituality and the influence of context on children’s spiritual lives. The findings demonstrated the significance of the teachers’ own awareness of spirituality and the importance of the teacher–child relationship in acknowledging, responding to and supporting child spirituality.